Reduced immunogenicity of the mRNA vaccine BNT162b2 in patients with idiopathic pulmonary fibrosis. Issue 2 (3rd May 2022) - Karampitsakos, Theodoros; Papaioannou, Ourania; Dimeas, Ilias; Tsiri, Panagiota; Sotiropoulou, Vasilina; Tomos, Ioannis; Papanikolaou, Ilias C.; Katsaras, Matthaios; Kirgou, Paraskevi; Daniil, Zoe; Gourgoulianis, Konstantinos I.; Sampsonas, Fotios; et al.
The emergence and spread of 2019 coronavirus disease (COVID-19) are causing a growing global public health crisis. Despite advances in treatment, vaccination remains the best way to contain the pandemic [1]. Vaccines are available by means of conditional marketing approval, full approval and emergency use authorisation pathways [2]. Evidence suggest that immunocompromised individuals, including solid-organ transplant recipients and patients under immunosuppressive treatment, may have increased mortality from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection despite double-dose mRNA vaccine regimens [3]. This is partially attributed to blunted immune responses to vaccination, since only 38–54% of kidney and liver transplant recipients developed detectable SARS-CoV-2 antibodies following the second dose of mRNA vaccines [3, 4]. Patients with #IPF do not mount appreciable anti-spike antibody responses to two doses of #SARSCoV2 mRNA vaccine compared to the general population. National authorities should prioritise patients with IPF for booster doses. https://bit.ly/3K2KXQ0